A Critical Evaluation of Speaking Activities in New Interchange (Fifth Edition) from a Task-Based Language Learning Perspective - Qonnita, Tsabita Rosaria; Haryati, Sri (Langkawi: Journal of The Association for Arabic and English, 2026)
This critical discourse study examines the extent to which speaking activities in a widely used international EFL textbook align with the core principles of task-based language learning (TBLL), such as task authenticity, learner interaction, focus on meaning, and outcome orientation. Grounded in the TBLL framework proposed by Ellis, Skehan, and Willis, the study systematically looks at eight conversation activities from New Interchange series (Fifth Edition), Student Books 3 and 3A. To triangulate the textbook analysis, semi-structured interviews were conducted with 17 secondary school learners to explore their perceptions of these speaking tasks. The findings reveal that although many activities simulate real-life communicative situations and encourage meaning-focused interaction, they often require pedagogical mediation to fully function as genuine tasks within a TBLL framework. The secondary school student participants reported higher levels of engagement, confidence, and perceived relevance when tasks were experienced as authentic, interactive, and goal-oriented. These findings accentuate the pivotal role of teacher mediation in transforming textbook-based activities into meaningful communicative experiences. Our findings call for more meaningful speaking tasks that impact on students’ oral ability in English.